Religious Moderation in the Perspective of Sufism: Abd Karim Al-Jilli’s Idea of Religious Tolerance - Muhammad Agil Munawwar; Ahmad Jamin (Studi Multidisipliner: Jurnal Kajian Keislaman, 2026)
This study aims to analyze the concept of religious tolerance from the perspective of Sufi Abd al-Karim al-Jilli and its relevance to religious moderation in Indonesia. Although many studies on tolerance and Sufism have been conducted, there are still research gaps in systematically linking the metaphysical framework of al-Jilli, especially through the concept of al-Insan al-Kamil, with the problem of contemporary religious intolerance in Indonesia. This research focuses on three main aspects, namely: (1) the conceptualization of tolerance according to al-Jilli, (2) his views on religious and social diversity, and (3) the relevance of his thinking in the context of religious life in Indonesia today. This research uses a qualitative approach with the type of library research, by utilizing primary sources in the form of al-Jilli's works, especially al-Insan al-Kamil, and supported by relevant secondary literature. Data analysis is carried out through a thematic content analysis approach with coding, categorization, and interpretation stages. The results of the study show that the concept of tolerance of al-Jilli is rooted in an esoteric-universalistic view that views the plurality of religions within the framework of the unity of divine reality. However, this view is not interpreted as an equalization of all religions, but rather as an ethical basis for respecting differences without eliminating theological boundaries. This research provides a theoretical contribution in the form of a more systematic interpretation of the concept of tolerance within the framework of al-Jilli's Sufism metaphysics, as well as a practical contribution in the form of an interpretive framework that can be used in strengthening the academic position while increasing the relevance of al-Jilli's thought in responding to the dynamics of contemporary diversity.